Long-term evaluation of surface topographic and topsoil grain composition changes in an agricultural landscape - Halászová, Klaudia; Lackóová, Lenka; Panagopoulos, Thomas (Frontiers in Environmental Science, 2024)
This study investigates long-term changes in topography and topsoil grain composition within an agricultural landscape in south-western Slovakia. Using high-precision positioning measurements and airborne laser scanning, digital terrain models (DTM) were created for the years 2011, 2017 and 2020. Grain size analyses of soil samples from three time periods M1 (1961-1970), M2 (2009-2015) and M3 (2015-2016) showed changes in soil texture due to wind erosion. The dominant soil types changed from loam and clay loam to silty loam over the study periods, highlighting wind erosion impact. Comparison of the DTMs, quantified the topographic changes showing different ratios of accumulation and deflation processes. The windbreak significantly reduces soil erosion by reducing wind speed and promoting soil accumulation up to 80 m windward and 20 m leeward. Notable changes in soil composition included decrease in clay and silt content and an increase in sand content. The study highlights the complex interplay of climatic and wind factors in shaping the topography, soil properties and emphasises the protective role of windbreaks in agricultural landscapes over time.